Remdesivir targets a structurally analogous region of the Ebola virus and SARS-CoV-2 polymerases - Lo, Michael K. (Proc Natl Acad Sci U S A, 2020)
Remdesivir is a broad-spectrum antiviral nucleotide prodrug that has been clinically evaluated in Ebola virus patients and recently received emergency use authorization (EUA) for treatment of COVID-19. With approvals from the Federal Select Agent Program and the Centers for Disease Control and Prevention’s Institutional Biosecurity Board, we characterized the resistance profile of remdesivir by serially passaging Ebola virus under remdesivir selection; we generated lineages with low-level reduced susceptibility to remdesivir after 35 passages. We found that a single amino acid substitution, F548S, in the Ebola virus polymerase conferred low-level reduced susceptibility to remdesivir. The F548 residue is highly conserved in filoviruses but should be subject to specific surveillance among novel filoviruses, in newly emerging variants in ongoing outbreaks, and also in Ebola virus patients undergoing remdesivir therapy. Homology modeling suggests that the Ebola virus polymerase F548 residue lies in the F-motif of the polymerase active site, a region that was previously identified as susceptible to resistance mutations in coronaviruses. Our data suggest that molecular surveillance of this region of the polymerase in remdesivir-treated COVID-19 patients is also warranted.